MANAJEMEN SDM BERBASIS PSIKOLOGI POSITIF DALAM MENINGKATKAN EFEKTIVITAS TENAGA KESEHATAN DIBIDANG FARMASI DI ERA SOCIETY 5.0 - Idaayupebrina; Lisdayanti Aulia Putri; Khuzaini; Syahrial Shaddiq (PT. Hasba Edukasi Mandiri, 2025)
The Society 5.0 era demands that health professionals, particularly in the pharmaceutical sector, work quickly, accurately, and humanely in delivering services to the public. Amid these demands, the effectiveness of pharmaceutical personnel becomes a key factor in the success of healthcare institutions. This study aims to examine the role of human resource management (HRM) based on positive psychology in enhancing the effectiveness of healthcare professionals in the pharmaceutical field. Pharmaceutical health workers face complex challenges that require high levels of effectiveness—not only in technical aspects but also in interpersonal skills and psychological resilience. This article is a conceptual study that seeks to explain how a positive psychology-based HRM approach can be utilized to improve the effectiveness of pharmaceutical health personnel.